Application of a new vitamin D blood test on the Emirati population. Issue 180 (June 2018) - shah, Iltaf; Al-Dabbagh, Bayan; Gariballa, Salah; Al-Menhali, Asma; Muhammad, Neak; Yasin, Javed; Ashraf, S. Salman
Graphical abstract: Highlights: An LC–MS/MS method was developed to quantify 10 vitamin D metabolites. Our method can separate co-eluting inactive epimers and isobars from the active forms of vitamin D. This method was used to quantify active forms of vitamin D metabolites in a sample of the Emirati population. Our results show that the Emirati population has very low levels of 25-hydroxy vitamin D. Abstract: Research shows that immunoassay techniques are not the best choice for the estimation of vitamin D in human blood samples. The main reasons are that some immunoassays are not able to distinguish between 25-OHD3 and 25-OHD2 vitamin D metabolites. Furthermore, immunoassays cannot differentiate between 25OHD and inactive epimers of vitamin D. Vitamin D epimers and isobars have been known to overlap with the 25OHD signals and give false positives when tested. Liquid chromatography tandem-mass spectrometry (LC–MS/MS) can differentiate between 25OHD3 and 25OHD2. Separating epimers and isobars (which have the same molecular weight) from vitamin D is achieved through chromatographic separation from actual 25OHD peaks, although this could also cause inaccuracies in vitamin D measurements. The main aim of this study was to develop and validate an improved LC–MS/MS method (using a Shimadzu 8060 system) that could accurately detect and quantitate up to 10 different metabolites of vitamin D, as well as differentiate the epimers and isobars. The secondary aim was to apply the developed LC–MS/MS method for the accurate measurement of blood vitamin D levels in the Emirati population. The Shimadzu 8060 system was run using positive ion electrospray ionization (ESI) in Dynamic Multiple Reaction Monitoring (DMRM) mode for quantification. The method involved blood sample collection from 80 Emirati volunteers, followed by serum extraction and liquid–liquid extraction. The chromatography column used for the analysis was an Ascentis Express F5. Precursor and product ions were detected using a Shimadzu 8060 LC–MS/MS system, and 10 metabolites of vitamin D were detected and quantified, including epimers and isobars. The method validation showed good sensitivity, recovery, linearity, precision, specificity, and accuracy. Furthermore, the data showed that vitamin D epimer 3-epi-25OHD and isobar 7-α-hydroxy-4-cholesten-3-one (7αC4) accounted for a significant portion of vitamin D results in the Emirati population. We report a more reliable, reproducible, and robust LC–MS/MS method for the accurate detection of 25OHD (vitamin D) in the Emirati population. The method has the capacity to detect and separate 10 metabolites of vitamin D as well as separate 25OHD from co-eluting epimers and isobars. The method has also been successfully implemented in gauging vitamin D deficiency in the Emirati population. Thus, this improved LC–MS/MS method could prove very useful in accurately estimating the levels of vitamin D in the Emirati population and in further clinical studies.